2020
DOI: 10.1108/jbim-01-2020-0021
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of relational embeddedness: mediating roles of influence strategies in managing marketing channel opportunism

Abstract: Purpose The purpose of this study is to develop a better understanding of how relational embeddedness offers marketing channel partners both benefits and hazards. The nonlinear effect of relational embeddedness on channel opportunism is investigated. Influence strategies (i.e. coercive and noncoercive influence) are also examined as mediators of this nonlinear effect. Design/methodology/approach Survey data are gathered from a sample of 149 manufacturers in China. The hypotheses are tested through regression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 126 publications
(224 reference statements)
2
8
0
Order By: Relevance
“…For example, formal control inhibits opportunism (Wei et al. , 2022), while Zhou et al. (2021) have found that formal control has an inverted U-shaped effect on opportunism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, formal control inhibits opportunism (Wei et al. , 2022), while Zhou et al. (2021) have found that formal control has an inverted U-shaped effect on opportunism.…”
Section: Discussionmentioning
confidence: 99%
“…Most relevant research on opportunism studies the role of independent antecedents on opportunism (Feng et al, 2020). For example, formal control inhibits opportunism (Wei et al, 2022), while Zhou et al (2021) have found that formal control has an inverted U-shaped effect on opportunism. The results of this study can explain the contradictory conclusions of existing studies, which may be due to the neglect of correlations among multiple antecedents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our findings align with Sheng et al (2018), who find that both contractual and relational governance is essential to reduce opportunism in China. Interestingly, Zhou et al (2021) found a U-shaped association between relational embeddedness and opportunism in Chinese B2B relationships, i.e. relational mechanisms are instrumental in addressing opportunism.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, Zhang et al (2019) demonstrated a lack of impact of servitization on performance. Using data from 143 servitized Chinese manufacturers, Zhou et al (2020) investigated how a manufacturer's service supply network moderates the effect of performance on servitization. Their findings suggested that servitization has a U-shaped relationship with a manufacturer's financial performance.…”
Section: Servitization and Performancementioning
confidence: 99%